Effects of Intravenous Dexmedetomidine on Sensory and Motor Block Characteristics in Adults Undergoing Infraumbilical Surgery Under Subarachnoid Block - Dwivedi, Neha; Choudhuri, Pratiti; Nayar, Pavan (Journal of the Portuguese Society of Anesthesiology, 2025)
Introduction: Subarachnoid block is enhanced by intrathecal administration of adjuvants (opioids, α2-agonists, etc.) with bupivacaine. A potent α2-agonist, dexmedetomidine, causes sedation and analgesia when administered intravenously. Its intrathecal use is not approved. This study was designed to evaluate the effects of intravenous dexmedetomidine on subarachnoid block (SAB). Methods: Sixty patients of the American Society of Anesthesiologists grade 1-2, of either sex, aged 18–60 years, undergoing infraumbilical surgery under SAB were randomized into two groups, group-C receiving 50 mL normal saline and group-D receiving dexmedetomidine infusion (0.5 mcg/kg in 50 mL normal saline) over 15 minutes within two minutes of SAB. The onset and duration of sensory and motor blocks were measured. Heart rate (HR), systolic (SBP), diastolic (DBP), and mean arterial pressure (MAP) were taken preoperatively, at SAB, 2, 4, 6, 8, 10, 15, 20, 25, 30, 45, 60, 90, and 120 minutes after SAB. Intraoperative sedation was assessed pre-drug infusion (post-SAB) and 30 and 60 minutes after SAB. Postoperative pain and sedation were assessed at 1, 2, 4, 8, 12 and 24 hours. Results: Group-D showed a faster onset of sensory block and longer sensory and motor block than group-C (p<0.05). The onset of motor block was comparable between the groups. Group-C showed higher HR, SBP, DBP, and MAP than group-D (p<0.05). Group-D had higher sedation scores and less postoperative pain than group-C (p<0.05). Conclusion: Dexmedetomidine causes a faster onset of sensory block, prolonged sensory and motor blocks with stable hemodynamics, better sedation, and postoperative analgesia.